Association between LMP2 and LMP7 gene polymorphisms and the risk of gastric cancer: A case-control study - MA, XIANG (Oncol Lett, 2015)
The integrality of low molecular weight protein (LMP)2/LMP7 function plays an important role in the processing of GC cell antigens. The purpose of the present hospital-based case-control study was to estimate the effect of polymorphisms in the LMP2 and LMP7 genes on the risk of GC. Polymerase chain reaction-restriction fragment length polymorphism analysis was used to distinguish the Arg to His substitution at codon 60 of LMP2 (LMP2-60) and the Gln to Lys substitution at codon 145 of LMP7 (LMP7-145) in 502 gastric cancer patients and 502 age and gender-matched cancer-free control individuals. The Lys allele of the LMP7-145 variant was more frequent in GC patients compared with control individuals [P=0.004; adjusted odds ratio (OR), 1.39; 95% confidence interval (CI), 1.11–1.74]. The Gln/Lys and Lys/Lys genotypes increased the risk of GC compared with the Gln/Gln genotype (P=0.049 and P=0.041, respectively; adjusted OR, 1.32 and 2.13, respectively; 95% CI, 1.00–1.73 and 1.03–4.39, respectively). Compared with the Gln/Gln genotype, the LMP7-145 Gln/Lys and Lys/Lys variants of the LMP7 gene were also associated with increased susceptibility to GC (P=0.017; adjusted OR, 1.38; 95% CI, 1.06–1.80). Haplotype analysis revealed that the LMP2 (Arg)-LMP7 (Lys) haplotype was associated with increased risk of GC (P=0.013, adjusted OR=1.34, 95% CI=1.06–1.70). Stratified analysis revealed that the association between the risk of GC and the variant genotypes of LMP7-145 was stronger in older individuals (>59 years), males and non-smokers. However, no association between the LMP2-60 polymorphism and the risk of GC was observed. The present results suggest that the LMP7-145 genetic variant contributes to increased susceptibility to GC, and the Lys allele is an independent risk factor for GC.